Single Center Retrospective Analysis of Conventional and Radial TIG Catheters for Transradial Diagnostic Coronary Angiography. (8th September 2015) - Vorpahl, Marc; Koehler, Till; Foerst, Jason; Panagiotopoulos, Spyridon; Schleiting, Heinrich; Koss, Klaus; Ziegler, Gunda; Brinkmann, Hilmar; Seyfarth, Melchior; Tiroch, Klaus
Abstract : Current guidelines favor the radial approach for coronary angiography. Therefore, specialty radial diagnostic catheters were designed to engage both coronary arteries with a single device. However, it is unclear if single catheters are superior to conventional catheters. A retrospective analysis was performed of consecutive right radial coronary angiographies to determine catheter use, fluoroscopy time, radiation dosage, and consumption of contrast. Procedures were performed with a single TIG catheter or conventional catheters (CONV). Procedures with coronary artery bypass grafts or ventricular angiographies were excluded. 273 transradial procedures were performed successfully. 95 procedures were performed with CONV and 178 procedures with a TIG. Crossover to additional catheters was higher in TIG (15.2%) compared to CONV (5.3%, p = 0.02 ). Fluoroscopy time was comparable between CONV and TIG, without crossover (2.2 ± 1.2 min versus2.3 ± 1.2 min; n.s.), however, greater in the case of crossover for CONV (5.8 ± 0.7 ) and TIG (7.6 ± 3.0 ;p = 0.0001 ). Radiation dosage was similar in CONV and the TIG, without crossover (1419 ± 1075, cGy∗ cm 2 versus1690 ± 1138 ; n.s.), however, greater for CONV (2374 ± 620 ) and TIG (3733 ± 2281, p = 0.05 ) with crossover. Overall, the amount of contrast was greater in TIG (56 ± 13 mL) versus CONV (48 ± 3 mL;p = 0.0003 ). CONV femoral catheters may be the primary choice for radial approach.